Accountability in Managing Business Funds through Budgeting to SME’s - I Gusti Ketut Agung Ulupui; Siti Fatimah Zahra; Dwi Handarini (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The classic problem that is still inherent in SME’s activities is the lack of capital. This is also felt by SMEs in the Tarumajaya sub-district, North Bekasi, West Java. So, there is a need for appropriate fund management and budgeting. Therefore, this activity aims to provide workshops related to accountability, good procedures for managing business funds, as well as providing budgeting practices for SMEs. The method of implementing PKM activities consists of 3 stages, namely: planning, implementation, and evaluation. The workshop was held in the Hall of TPI PALIJAYA Segara Jaya Village and was attended by 54 business people with different business objects. The material was delivered in the form of theory and practice, followed by a discussion and question and answer session with the participants. Based on the results of the questionnaire survey, it was found that before this training, only 23% of the trainees stated that they had planned a business activity budget. Only 17% stated that they used to record transactions related to their business activities routinely. After this training, the participants increasingly understood the importance of budgeting in business. Thus, an assessment of 90% of participants stated that the business budget was an important matter. As for the participant’s assessment of the whole set of activities, 83% stated that the material presented by the service team was important, and 77% stated it was useful. As many as 73% of participants stated that the material had been delivered by the service team clearly, and 87% of participants expressed satisfaction with the community service activities carried out by the community service team from FE UNJ.